Reactivity of Diarylnitrenium Ions. Issue 41 (7th July 2020) - Kütt, Agnes; Jeschke, Gunnar; Toom, Lauri; Nerut, Jaak; Reed, Christopher A.
Abstract: Hydride abstraction from diarylamines with the trityl ion is explored in an attempt to generate a stable diarylnitrenium ion, Ar2 N + . Sequential H‐atom abstraction reactions ensue. The first H‐atom abstraction leads to intensely colored aminium radical cations, Ar2 NH .+, some of which are quite stable. However, most undergo a second H‐atom abstraction leading to ammonium ions, Ar2 NH2 + . In the absence of a ready source of H‐atoms, a unique self‐abstraction reaction occurs when Ar=Me5 C6, leading to a novel iminium radical cation, Ar=N .+ Ar, which decays via a second self H‐atom abstraction reaction to give a stable iminium ion, Ar=N + HAr. These products differ substantially from those derived via photochemically produced diarylnitrenium ions. Abstract : Nitrenium conundrum : When exploring synthetic‐scale generation of stable diarylnitrenium ions, Ar2 N +, we find products quite different to those derived from photochemical generation.